Effectiveness of integrating the systematic and visual approaches in acquiring the tenth grade students with physics concepts - Sulaiman, Mohammad; Abdullah, Abdulrazzaq (Humanities Journal of University of Zakho, 2023)
The study aims to identify the effectiveness of integrating the systematic and visual approaches in acquiring the tenth grade students with physics concepts.The sample consisted of (142) male and female students who were deliberately selected from the research community in Zakho city for the academic year (2021-2022), then, they were divided into four equal groups in a number of variables according to the factorial design(2*2), two experimental groups (males, females) studied the subject according to the integration of the two entrances, and the other two controls (males, females) studied the same subject according to the usual method. In order to achieve the aim of the study and test its main hypotheses and its fields, the researchers prepared the first is a test to acquire physics concepts in its final form of (30) objective paragraphs of the two types of pairing and multiple choice of three alternatives, the tool was characterized by validity, stability and psychometric characteristics. After that, the researchers prepared a number of teaching plans for the experimental and control research groups, and then assigned the teaching of these groups to the subject’s teacher in the schools specified for the experiment. The results indicated as follows: There is a statistically significant difference at the level (0.05) between the averages of the four research groups' acquisition of physics concepts according to the method variable and in favor of the two experimental groups. There is no statistically significant difference at the level (0.05) between the averages of the four research groups' acquisition of physics concepts according to the gender and the interaction between two variables. In the light of the study results, the researchers came out with a number of implementations and recommendations for further studies.